Somatosensory impairments in patients with multiple sclerosis: association with dynamic postural control and upper extremity motor function. (2nd April 2020) - Dogru Huzmeli, Esra; Duman, Taskin
Abstract: Purpose: We planned this study to bring attention to the somatosensory impairments in patients with multiple sclerosis (PwMS) and to investigate relationship of somatosensory impairments with dynamic postural stability and upper extremity motor function. Methods: Seven males and 23 females, 30 patients with mean EDSS 2.9 (SD = 1.4), aged between 18 and 65 years (mean = 41.43 ± 14.90 years) were included in this clinical study. Light touch sensorial assessment was made with Semmes Weinstein monofilament test and proprioception by distal proprioception test. Hand strength was measured by the Jamar dynamometer, fine motor skill was examined with nine-hole peg test, functional reach test in sitting and standing position was applied. Nottingham Extended Activities of Daily Living Scale (NEADLS) was used to measure everyday activities. Results: We found a negative and moderate correlation between FRT in standing and light touch of the middle of the heel (right: –0.515), metatarsal bone (right r : 0.453, left r : –0.426), and medial of the foot (right r : –0.462). There was a negative and moderate correlation between NEADLS and light touch of the metatarsal bone (right r : –0.564, left r : –0.472), medial of the foot (right r : –0.531, left r : –0.479), and lateral of the foot (right r : –0.526). We found a positive and moderate correlation between proprioception of the ankle (right r : 0.421 left r : 0.588) and NEADLS. Conclusions: We found impairment in light touch and proprioception and, associations between sensorial functions and dynamic postural stability in PwMS. Also impaired sensorial functions cause dependent patients in daily living activities. In the assessment of balance and falling risk, independency in daily living activities; foot light touch and proprioception sense should be taken into account, hence it may provide guidance in planning rehabilitation programmes. Abbreviations: MS: multiple sclerosis; PwMS: patients with multiple sclerosis; VAS: visual analogue scale; FRT: functional reach test; 9-HPT: Nine-hole peg test; EDSS: The Expanded Disability Status Scale; NEADLS: Nottingham Extended Activities of Daily Living Scale